PEDAGOGICAL THEATRE METHOD WITHIN THE MULTISENSORY APPROACH IN CAREER EDUCATION AT SCHOOL - Šmite, Jolanta; Dišlere, Vija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Career is an important area of life, the development of which should be developed as early as school years. It is important to help a student get as much information as possible about opportunities in their career choices from the start of primary school, help them find the right direction for them, knowing their desires, skills and talents. Insufficient methodological support for primary school pupils in early stages of career education determines the problem of the study. The aim of the study is to theoretically investigate the Pedagogical Theater Method, to develop a Multisensory Approach Scheme Using the Theater Method to promote the development of students' sensory awareness in career education in the 5th Grade. A 24 pupil’s survey was conducted, descriptive statistics were used for data processing. Pedagogical theater method develops the skill of using the senses (sight, hearing, taste, smell or touch) and using real life experience, thus expanding opportunities for self-discovery and choosing a potential future career. The Multi-Sensory Approach, when several senses are stimulated at the same time, methodically using purposefully prepared tasks, promotes the development of students' sensory awareness, which can be used in career education and choosing a future profession. The Pedagogical Theater Method organically fits into the implementation scheme of the Multisensory Approach in Career Education for the 5th Grade. The Pedagogical Theater Method is suitable for the implementation of career education in work with pupils.